REPRESENTASI FRAME DALAM LATAR BELAKANG WACANA TAJUK TENTANG TERORISME - P Ari Subagyo (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to describe the representations of frames in the backgrounds of editorials on terrorism. It uses the critical pragmatic approach combining pragmatics andcritical discourse analysis (CDA). There are three frames in the editorials on terrorism infour national dailies in Indonesia (Suara Pembaruan, Republika, Kompas, and Koran Tempo)in accordance with their ideologies (historical backgrounds and affiliations). The studyproves that the three frames are systematically represented in the backgrounds of editorialson terrorism. Suara Pembaruan, Republika, Kompas, and Koran Tempo represent their framesin their own ways. Each daily uses the background to present information or opinionsaccording to its frame.